Hispanic physicians' tobacco intervention practices: a cross-sectional survey study - Urrutia-Rojas Ximena; Ed Hsu Chiehwen; Jacobson Holly E; Papenfuss Richard L; Soto Mas Francisco G; Kane William M (BMC, 2005)
Abstract Background U.S. Hispanic physicians constitute a considerable professional collective, and they may be most suited to attend to the health education needs of the growing U.S. Hispanic population. These educational needs include tobacco use prevention and smoking cessation. However, there is a lack of information on Hispanic physicians' tobacco intervention practices, their level of awareness and use of cessation protocols, and the type of programs that would best address their tobacco training needs. The purpose of this study was to assess the tobacco intervention practices and training needs of Hispanic physicians. Methods Data was collected through a validated survey instrument among a cross-sectional sample of self-reported Hispanic physicians. Data analyses included frequencies, descriptive statistics, and factorial analyses of variance. Results The response rate was 55.5%. The majority of respondents (73.3%) were middle-age males. Less than half of respondents routinely performed the most basic intervention: asking patients about smoking status (44.4%) and advising smoking patients to quit (42.2%). Twenty-five percent assisted smoking patients by talking to them about the health risks of smoking, providing education materials or referring them to cessation programs. Only 4.4% routinely arranged follow-up visits or phone calls for smoking patients. The majority of respondents (64.4%) indicated that they prescribe cessation treatments to less than 20% of smoking patients. A few (4.4%) routinely used behavioral change techniques or programs. A minority (15.6%) indicated that they routinely ask their patients about exposure to tobacco smoke, and 6.7% assisted patients exposed to secondhand smoke in understanding the health risks associated with environmental tobacco smoke (ETS). The most frequently encountered barriers preventing respondents from intervening with patients who smoke included: time, lack of training, lack of receptivity by patients, and lack of reimbursement by third party payers. There was no significant main effect of type of physician, nor was there an interaction effect (gender by type of physician), on tobacco-related practices. Conclusion The results indicate that Hispanic physicians, similarly to U.S. physicians in general, do not meet the level of intervention recommended by health care agencies. The results presented will assist in the development of tobacco training initiatives for Hispanic physicians.